Emphatic Italics in English Translations: Stylistic Failure or Motivated Stylistic Resources? - Saldanha, Gabriela (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
This article argues that emphatic italics, a typographic feature regularly ignored by linguists and associated with poor style, have an important stylistic function in English, often working in implicit association with prosodic patterns in spoken language to signal marked information focus, thus fulfilling an important role in information structure and adding a conversational and involved tone to written texts. Emphatic italics are more common in English than in other languages because tonic prominence is the preferred means of marking information focus in English, while other languages use purely linguistic devices, such as word order. Thus arises the question of what happens in English translations from and into other languages. The study presented here looks at results obtained from a bidirectional English-Portuguese corpus (COMPARA) which suggest that italics may be less common in English translations from Portuguese than in non-translated English texts. This trend could potentially be explained by the use of common features of translated language, in particular explicitation and conservatism (also known as normalization). However, a closer look at the work of particular translators shows that the avoidance or use of italics is not a consistent feature of translations and may be a characteristic feature of the stylistic profile of certain translators.